NET INTERACTION OF INSTITUTIONS OF HIGHER EDUCATION AND VOCATIONAL EDUCATION WHILE IMPLEMENTING PROGRAMMES OF "APPLIED BACCALAUREAT" - Alexander I. Chuchalin; Tatyana S. Petrovskaya; Oksana S. Chernova (Moscow Polytechnic University, 2022)
"Applied" bachelor degree programs have to provide for the graduates practical training specificfor vocational education and theoretical education specific for the programs of higher education on the level of the "academic" bachelor degree programs. The paper is focused on the potential trends and conditions of such programs implementation. The specific features of the structure and content of the educational programs are defined on the basis of the comparative analysis of requirements for learning outcomes (competences) of the graduates of "academic" bachelor degree programs, vocational education programs and "applied" bachelor degree programs.